2006
DOI: 10.1111/j.1365-2842.2005.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic damage in human peripheral lymphocytes exposed to mineral trioxide aggregate and Portland cements

Abstract: summary Mineral trioxide aggregate (MTA) and Portland cement are being used in dentistry as root-end-filling material for periapical surgery and for the sealing of communications between the root canal system and the surrounding tissues. However, genotoxicity tests for complete risk assessment of these compounds have not been conducted up to now. In the present study, the genotoxic effects of MTA and Portland cements were evaluated in peripheral lymphocytes from 10 volunteers by the alkaline single cell gel (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Therefore, and taking into account the lack of data currently available, the assessment of the potential genotoxicity of CEM is justified. In addition, it has been reported in previous studies that MTA has no cytotoxic 7,31,32) and no genotoxic 15,20,33,34) effects in vitro. For these reasons, the aim of this study was to evaluate the biocompatibility of CEM compared with MTA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, and taking into account the lack of data currently available, the assessment of the potential genotoxicity of CEM is justified. In addition, it has been reported in previous studies that MTA has no cytotoxic 7,31,32) and no genotoxic 15,20,33,34) effects in vitro. For these reasons, the aim of this study was to evaluate the biocompatibility of CEM compared with MTA.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Ribeiro and coworkers have demonstrated that the single-cell gel (comet) assay is one of the suitable tools to investigate the genotoxicity of compounds used in dental practice [17][18][19] . Previous studies have demonstrated that MTA, whether gray or white, cannot induce geno-or cytotoxicity in mouse lymphoma or Chinese hamster ovary (CHO) cells, even after exposure to human peripheral lymphocytes ex vivo 20,21) . Taking into consideration that fibroblasts are in direct contact with MTA or CEM over extended periods of time 2) , it would be interesting to know whether, and to what extent, these two materials can exert geno-and/ or cytotoxic effects in fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Braz et al assessed the genotoxic effects of MTA in lymphocytes and failed to detect DNA damage. 42 Camargo et al revealed that…”
mentioning
confidence: 99%